An integrated decision– making approach for improving European air traffic management - GRUKSHA-COCKAYNE, Yael (Institutional Knowledge at Singapore Management University, 2008)
We develop a multistakeholder, multicriteria decision-making framework for Eurocontrol, the European air traffic management organization, for evaluating and selecting operational improvements to the air traffic management system. The selected set of improvements will form the master plan of the Single European Sky initiative for harmonizing air traffic, in an effort to cope with the forecasted increase in air traffic, while maintaining safety, protecting the environment, and improving predictability and efficiency. The challenge is to select the set of enhancements such that the required performance targets are met and all key stakeholders are committed to the decisions. In this paper, we develop and implement a model to identify a preferred set of improvements to the arrival and departure procedures to and from airports. We provide an integrated approach for valuing a large number of alternatives, while considering interactions among them. The model combines quantitative and qualitative expert assessments of the possible enhancements and identifies commonalities and differences in the stakeholders' perspectives, ultimately recommending a preferred course of action. The model is currently being adopted by Eurocontrol as the formal trade-off analysis methodology supporting all enhancements' decision-making discussions throughout the construction of the master plan.